2008
DOI: 10.1097/mao.0b013e318184601a
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Vascular Decompression

Abstract: Endoscopic vascular decompression for patients with vascular compressive syndromes such as TGN and HFS is a safe and equally effective procedure when compared with the traditional and widely successful MVD surgery, with the added benefit of less morbidity and shorter hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…2,7,11,21,24 All report excellent safety and short-to medium-term functional results. The largest of these, by Kabil et al, reported results for 255 patients with a favorable 3-year success rate and a lower rate of complications when compared with published series of microscopic MVD.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,11,21,24 All report excellent safety and short-to medium-term functional results. The largest of these, by Kabil et al, reported results for 255 patients with a favorable 3-year success rate and a lower rate of complications when compared with published series of microscopic MVD.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, better surgical outcome is attributed to an increased identification of neurovascular conflicts during surgery. On the other hand, many authors find similar surgical outcome with and without the aid of the endoscope, or do not compare their results to outcomes of conventional MVDs [10,27].…”
Section: Symptom Reliefmentioning
confidence: 93%
“…Hence, we could not delineate to what extent symptoms such as facial numbness, dizziness, hearing impairment, and tinnitus, were present prior to surgery, and to what extent it was aggravated by MVD. Many authors advocate the use of eaMVD or pure endoscopic vascular decompression on the basis of lower incidence of complications [6,17,[27][28][29], but others do not find a decline in the complication rates due to the inclusion of the endoscope [8,10].…”
Section: Complication Profilementioning
confidence: 98%
“…The applications of the neuroendoscope are quickly escalating in neurosurgery and otological surgery, so it is vital that optimal surgical techniques are used. The expanding literature on endoscopic MVD supports the use of the endoscope as a tool that provides excellent results with a low rate of complications [6,7,8]. …”
Section: Resultsmentioning
confidence: 99%
“…endoscope-assisted microsurgery [5]. We hypothesized that a fully endoscopic procedure would provide an unobstructed panoramic view of the CPA [6,7,8], allowing for a less traumatic, minimally invasive approach to the site of vascular pathology [7,9]. …”
Section: Introductionmentioning
confidence: 99%